2021
DOI: 10.1161/atvbaha.120.314557
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial HMGB1 Is a Critical Regulator of LDL Transcytosis via an SREBP2–SR-BI Axis

Abstract: OBJECTIVE: LDL (low-density lipoprotein) transcytosis across the endothelium is performed by the SR-BI (scavenger receptor class B type 1) receptor and contributes to atherosclerosis. HMGB1 (high mobility group box 1) is a structural protein in the nucleus that is released by cells during inflammation; extracellular HMGB1 has been implicated in advanced disease. Whether intracellular HMGB1 regulates LDL transcytosis through its nuclear functions is unknown. Approac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
4
2

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 41 publications
0
32
0
Order By: Relevance
“…Estradiol inhibited endothelial SR-BI through activation of the G-protein coupled estrogen receptor and thereby LDL transport [ 34 ]. Similarly, the proinflammatory mediator high mobility group box 1 (HMGB1) regulated LDL transcytosis via SR-BI [ 35 ]. Whether these pathways also influence HDL transport is unknown and remains to be investigated.…”
Section: Hdl Transport Through Endothelial Cellsmentioning
confidence: 99%
“…Estradiol inhibited endothelial SR-BI through activation of the G-protein coupled estrogen receptor and thereby LDL transport [ 34 ]. Similarly, the proinflammatory mediator high mobility group box 1 (HMGB1) regulated LDL transcytosis via SR-BI [ 35 ]. Whether these pathways also influence HDL transport is unknown and remains to be investigated.…”
Section: Hdl Transport Through Endothelial Cellsmentioning
confidence: 99%
“…Additionally, Hi-C data demonstrated that HMGB1 binds to TAD (Topology Associated Domain) boundaries, known to regulate chromatin topology and consequently gene expression. In addition to this paper, a recent study has also evoked an RNA-binding property as a another functional layer for HMGB1 to regulate gene expression (26,43). Therefore, 3-D conformation and RNA binding clearly represent additional mechanisms by which HMGB1 could mediate its repressive effect on LXRα, which is therefore worthwhile to further investigate in the context of liver steatosis.…”
Section: Discussionmentioning
confidence: 78%
“…5) signi cantly promoted Dil-LDL accumulation with or without TNF . SR-BI, on the other hand, has been reported to faciliate AP to BL transport of LDL in an LDLR-independent manner [110]. However, there is some controversy about the role of LDLR in tra cking ligand across the brain endothelium.…”
Section: Discussionmentioning
confidence: 99%